Application of Human Factors Methods to Understand Missed Follow-up of Abnormal Test Results - Rogith, Deevakar; Satterly, Tyler; Singh, Hardeep; Sittig, Dean F.; Russo, Elise; Smith, Michael W.; Roosan, Don; Bhise, Viraj; Murphy, Daniel R. (Applied Clinical Informatics, 2020)
Objective This study demonstrates application of human factors methods for understanding causes for lack of timely follow-up of abnormal test results (“missed results”) in outpatient settings.Methods We identified 30 cases of missed test results by querying electronic health record data, developed a critical decision method (CDM)-based interview guide to understand decision-making processes, and interviewed physicians who ordered these tests. We analyzed transcribed responses using a contextual inquiry (CI)-based methodology to identify contextual factors contributing to missed results. We then developed a CI-based flow model and conducted a fault tree analysis (FTA) to identify hierarchical relationships between factors that delayed action.Results The flow model highlighted barriers in information flow and decision making, and the hierarchical model identified relationships between contributing factors for delayed action. Key findings including underdeveloped methods to track follow-up, as well as mismatches, in communication channels, timeframes, and expectations between patients and physicians.Conclusion This case report illustrates how human factors–based approaches can enable analysis of contributing factors that lead to missed results, thus informing development of preventive strategies to address them.
Keywords: contextual inquiry; fault tree analysis; abnormal laboratory follow-up; human factors; patient safety